2013
DOI: 10.1007/s00259-013-2367-1
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of FDG PET/CT in rectal cancer management: is it time to use the technique for early prognostication?

Abstract: # Springer-Verlag Berlin Heidelberg 2013 Colorectal cancer is the second leading cause of death and the fourth most commonly diagnosed cancer in the USA [1]. One form, rectal cancer, defined as cancer growing within 12 cm of the anal verge [2], is challenging because of its unique anatomical characteristics, critical position and therapeutic options (aimed at preserving pelvic floor integrity, sphincter continence and genitourinary functions). General considerations and staging proceduresWhen a patient is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…FDG-PET/CT is not routinely used in the staging of colorectal cancer, but could be proposed for problem solving, or in the presence of CEA elevation or resectable metastases [ 28 ], as proposed in the National Comprehensive Cancer Network guidelines (NCCN version 4.2013 [ 29 ]). Actually, for the local T staging, MRI and endorectal ultrasound (ERUS) are recommended [ 30 ]; for the detection of colorectal metastases (N and M staging), the most frequently used modalities are US, CT, MRI and FDG-PET/CT [ 31 ].…”
Section: Fdg-pet/ct For Tumor Stagingmentioning
confidence: 99%
“…FDG-PET/CT is not routinely used in the staging of colorectal cancer, but could be proposed for problem solving, or in the presence of CEA elevation or resectable metastases [ 28 ], as proposed in the National Comprehensive Cancer Network guidelines (NCCN version 4.2013 [ 29 ]). Actually, for the local T staging, MRI and endorectal ultrasound (ERUS) are recommended [ 30 ]; for the detection of colorectal metastases (N and M staging), the most frequently used modalities are US, CT, MRI and FDG-PET/CT [ 31 ].…”
Section: Fdg-pet/ct For Tumor Stagingmentioning
confidence: 99%
“…According to the National Comprehensive Cancer Network NCCN Guideline [4], PET/CT scanning is not routinely indicated both in the staging and in the follow-up of CRC, however it is indicated in the setting of serial increased CEA and resectable metastases, in order to identify other localizations and avoid invasive procedures [9]. Nevertheless, some investigators suggest that in certain clinical circumstances, like the initial staging of primary rectal cancer, FDG PET/CT could change the previous staging up to 39% of the patients and lead a management change in 18-24% of patients by demonstrating unsuspected metastatic disease or clarifying the nature of indeterminate lesions [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Of the available technologies, computed tomography (CT), magnetic resonance imaging (MRI), and endorectal ultrasound (ERUS) have evolved as the best modalities for accurately staging rectal cancer. In addition, fluorine-18 fluorodeoxyglucose positron emission tomography combined with computed tomography (PET/CT) is widely used not only for preoperative staging, but also for assessing the oncologic outcomes of rectal carcinoma [5-8]. Although several studies reported that the addition of 18 F-FDG PET/CT to conventional imaging methods might alter the treatment algorithm [9], in a recent study, Cipe et al concluded that routine use of 18 F-FDG PET/CT for preoperative staging does not impact the disease management of 96.8% of patients [10].…”
Section: Introductionmentioning
confidence: 99%